ANALISIS PENDAPATAN BERSIH PETANI KEDELAI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KEDELAI DI KECAMATAN BERINGIN KABUPATEN DELI SERDANG - Sahputra, Rahmaddin; Hasnudi, Hasnudi; Lubis, Mitra Musika (JURNAL AGRICA, 2012)
Abstract            This Research was conducted at sub-district of beringin as chosen location of research by reason the sub-district of Beringin is a central area of soybean production and as one of area for development of soybean in Regency of Deli Serdang. The objective of this research is to analyze the net income of soybean farmers in soybean agribusiness per planting season at sub-districtof Beringin and to analyze the influence of land, manpower, urea, TSP, KCl fertilizer and pesticide to the production of soybean per planting season in the sub-district of Beringin.                      This research applies field observation method by using research instrument, i.e. questionnaire and interview. The research is a quantitative descriptive study. The population in this research is all of famers who harvest of soybean at 3 (three) sample villages at the sub-district of Beringin. The respondent is 95 farmers as samples that distributied at village of karang anyar, Beringin and Serdang. The apllied data analysis mode is multi linear regression analysis that estimated by production function of cobb-douglas.            This result of research is conducted by using F-test that proved that the variable of land area (XI), manpower (X2), urea fertilizer (X3), TSP fertilizer (X4), KCl fertilizer (X5), and pesticide (X6) is significant to the soybean production variables. And on t-test, the land area, TSP fertilizer and pesticide influence the soybean production significantly. While the manpower, urea and KCl fertilizer has not significant influence to the production of soybean.            The conclusion of this research is the net income of soybean farmers per hectar/planting season at sub-district of Beringin is IDR 1.885.191 or 35 % of total cash income from the selling of 1.204,7 Kg while the production factor, i.e. land are TSP fertilizer and pesticide has a significant influence to the production of soybean at sub-district of Beringin. Keywords :   Production, Function of Production, Factor of Production, Estimation Model, Soybean, Production Elasticity, and Return to Scale.